Imaginaries around group abortion of marginalized pregnant adolescents in Mexico - Rangel-Flores, Yesica; Jimenez-Arroyo, Vanesa (Saúde e Sociedade, 2021)
The objective was to document the imaginations that abortion has in a group of pregnant adolescents in a marginal situation in Mexico, in order to identify whether the continuation of their pregnancies derives from a decision or from the absence of options to interrupt pregnancy. Qualitative-biographical study with individual interviews of twelve pregnant adolescents, which were audio-recorded and transcribed to subsequently carry out content analysis using the Krueger methodology. Abortion figures in her imagination as a desire but not as a strategy. Although most of them narrate having wished to lose the product of conception, none attempted to interrupt the pregnancy, guilt, fear of dying and the romanticization of motherhood were the main reasons why they decided to end their pregnancies. The study concludes that the challenges to access the interruption of pregnancy in adolescents become more complex in the framework of the existence of a series of cultural stereotypes built around the bodies and social function of women; which contributes to their resignation to the exercise of mothering without the physical, psychological and social capacities to do so.